Specific Influence of the Mountain Landscape on the Level of Intelligence, Worldview and National Character of the Mountain Peoples in the South Caucasus - Alizada Maleyka; Yarova Sevara (BIO Web of Conferences)
Today, against the backdrop of the rapidly growing globalization process, the study of ethnogenesis, lifestyle, mentality and worldview of the peoples of the world, as well as the establishment of their role in the development of human civilization has become extremely relevant. Scientific research conducted in recent years in the field of ethnography and ethnology have proven that among the many components involved in the formation and cultural development of the peoples of the world, the landscape of the area plays a special role and is of decisive importance. This article discusses this most important factor, which, using the example of the South Caucasus, predetermines the specificity of the highlanders in terms of their cultural and intellectual characteristics. In this regard, the article conducts relevant analyses that reveal the essence and significance of the natural and geographical components that form the specific appearance and way of thinking of the highlanders individually and the unique mentality of the ethnocultural community as a whole. In the conducted analyses, special attention is paid to those elements of the mountain environment that in various ways influence the psyche, views, passions, critical and creative thinking of the mountaineers. The article also reveals the subtle mechanism of the fusion of the soul of the mountaineer with his native nature and its components. The article also reveals the subtle mechanism of the fusion of the soul of the mountaineer with his native nature and its components. The identification of the unique features of the mountain peoples and the indication of the main reasons for this uniqueness are the leitmotif of this article.